Implementasi Pendidikan Karakter Islami Melalui Ekstrakurikuler Marawis Di Sekolah Dasar Assalam Kota Bandung - Wita Hidayati; Mohamad Yudiyanto; Ramdani, Peri (Prodi PGMI STAI Sabili Bandung, 2023)
The purpose of this study was to determine the impact of the implementation of Islamic character education through marawis exstracurricular activities at SD Assalam Bandung. The method used in this research is descriptive qualitative. Data collection technique by way of observation, interviews, and documentation. The result of Islamic Character education obtained through the marawis extracurricular are value education, namely Islamic character education, which upholds noble and commendable values, which includes three aspects, namely moral knowledge, moral attitude, and moral behavior. Thus, it can be said that the formation of Islamic character education through extracurriculer marawis for student at SD Assalam Bandungis quite effective. Seen from three indicatirs, namely motivation, enthusiasm, and excellent student achievement.